Freedom of expression: comparative analysis of the Malaysian Sedition Act 1948 / Mohammad Najmie Noordin and Darren Malis Jefferson - Noordin, Mohammad Najmie; Jefferson, Darren Malis (2005)
This thesis is a research on the limitations posed by the Sedition Act 1948 on the exercise of freedom of speech in Malaysia. Now after enjoying nearly five decades of independence, Malaysians are still haunted by the ghost of the past. With this research it is hope that many among the students and readers who were unaware of the graveness of such acts towards the future of our Malaysian way of life, could at least catch a glimpse of this pertinent issue. The primary objective is to observe, analyze and compare the exercise of the Sedition Act in Malaysia to that of in the United States and the United Kingdom and following such observation, we would like to put forth our findings and recommendation as to whether this Act is still relevant and necessary to be exercised in the Malaysian legal system.